Implementation Of M-Learning to Improve Learning Effectiveness In PAI Evaluation System Courses - Sa'idah, Nusrotus; Saefudin, Ahmad (Universitas Wahid Hasyim Semarang, 2024)
The digital era greatly influences learning activities and facilitates access to learning materials anywhere and anytime. Flexibility of learning, high interactivity, personalization of learning are the basic considerations of IT utilization. The purpose of this research is to develop an M-learning-based lecture room application in PAI evaluation courses. This study is a research and development (R & D) study with the ADDIE model. The subjects of this study were 5th semester students of PAI Study Program as many as 132 people. Sampling using saturated sample technique. Data collection used observation, interview and questionnaire distribution. Product validity is assessed by experts and students as a feasibility test using independent sample t test analysis. Assessment by expert judgment shows that the value is very good, namely an average of 4.67 by media experts. The results of the study with independent sample t-test showed a significance value of 0.00 probability with a significance of 0.05, which means that there is a significant difference between classes that use discussions and classes that are accompanied by the lecture hall application. This product has a very practical assessment by students as a reference for independent learning with an average score of 3.78. This M-Learning contributes more effectively and efficiently if done outside the classroom as a companion to independent learning.